Serine/Threonine‐Protein Kinase 3 Facilitates Myocardial Repair After Cardiac Injury Possibly Through the Glycogen Synthase Kinase‐3β/β‐Catenin Pathway - Ya‐Fei Li (Wiley, 2021)
Background The neonatal heart maintains its entire regeneration capacity within days after birth. Using quantitative phosphoproteomics technology, we identified that SGK3 (serine/threonine‐protein kinase 3) in the neonatal heart is highly expressed and activated after myocardial infarction. This study aimed to uncover the function and related mechanisms of SGK3 on cardiomyocyte proliferation and cardiac repair after apical resection or ischemia/reperfusion injury. Methods and Results The effect of SGK3 on proliferation and oxygen glucose deprivation/reoxygenation– induced apoptosis in isolated cardiomyocytes was evaluated using cardiomyocyte‐specific SGK3 overexpression or knockdown adenovirus5 vector. In vivo, gain‐ and loss‐of‐function experiments using cardiomyocyte‐specific adeno‐associated virus 9 were performed to determine the effect of SGK3 in cardiomyocyte proliferation and cardiac repair after apical resection or ischemia/reperfusion injury. In vitro, overexpression of SGK3 enhanced, whereas knockdown of SGK3 decreased, the cardiomyocyte proliferation ratio. In vivo, inhibiting the expression of SGK3 shortened the time window of cardiac regeneration after apical resection in neonatal mice, and overexpression of SGK3 significantly promoted myocardial repair and cardiac function recovery after ischemia/reperfusion injury in adult mice. Mechanistically, SGK3 promoted cardiomyocyte regeneration and myocardial repair after cardiac injury by inhibiting GSK‐3β (glycogen synthase kinase‐3β) activity and upregulating β‐catenin expression. SGK3 also upregulated the expression of cell cycle promoting genes G1/S‐specific cyclin‐D1, c‐myc (cellular‐myelocytomatosis viral oncogene), and cdc20 (cell division cycle 20), but downregulated the expression of cell cycle negative regulators cyclin kinase inhibitor P 21 and cyclin kinase inhibitor P 27. Conclusions Our study reveals a key role of SGK3 on cardiac repair after apical resection or ischemia/reperfusion injury, which may reopen a novel therapeutic option for myocardial infarction.